The impact of cardiogenic shock and out-of-hospital cardiac arrest on the outcome of acute myocardial infarction: a national-level analysis - Tomasov, Pavol; Motovska, Zuzana; Hlinomaz, Ota; Kala, Petr; Sramko, Marek; Mrozek, Jan; Hromadka, Milan; Precek, Jan; Bis, Josef; Matejka, Jan; Muzafarova, Tamilla; Cervinka, Pavel; et al. (Internal and emergency medicine, 2025)
Cardiogenic shock (CS) and out-of-hospital cardiac arrest (OHCA) are events with profound implications for patient outcomes. We aim to analyze the predictors of CS and OHCA in patients with acute myocardial infarction and their effects on mortality. The analysis is based on data from a national registry between 2016 and 2020. A total of 23,703 patients with ST-elevation myocardial infarction (STEMI) were analyzed: (A) patients without CS and OHCA (19,590), (B) after OHCA (2,262), (C) with CS (713), and (D) after OHCA with CS (1,138). Patients after OHCA without CS had the lowest mean age [62.0 (± 12.6) years], while patients with CS without OHCA were the oldest [68.8 (± 11.8) years] and had the highest proportions of comorbidities. CS was a predictor of 30-day and 1-year mortality, with odds ratios [OR; 95% confidence intervals (CI)] of 5.52 (4.51; 6.75) and 4.66 (3.87; 5.61) for patients after OHCA, and OR (95% CI) 9.28 (7.56; 11.38) and 7.33 (6.04; 8.89) for those without OHCA. For overall survival up to 30 days and in comparison to patients without CS and OHCA, the hazard ratios (95% CI) was 2.77 (2.40; 3.20) for patients with OHCA only, 14.36 (12.57; 16.40) for patients with CS only, and 16.96 (15.19; 18.92) for patients with both CS and OHCA. OHCA altered the 30-day mortality risk after STEMI for both patients with and without CS. CS is a predictor of both 30-day and 1-year mortality in patients with STEMI, irrespective of OHCA status.
Keywords: Predictors; Out-of-hospital cardiac arrest; Acute myocardial infarction; Cardiogenic shock; Outcome